Research on gear reliability based on improved fourth moment - WANG ChunRong; ZHOU FuPing; XIA ErDong; GAO Hao (Jixie qiangdu)
Gear is the most commonly used transmission component, and its most common failure mode is tooth surface pitting and tooth root fracture. In order to analyze its reliability quickly and accurately, an improved fourth moment method considering failure correlation was proposed. Firstly, according to the failure mechanism, the reliability models of tooth contact fatigue and tooth root bending fracture failure were established respectively. Secondly, in order to improve the accuracy of the traditional fourth order moment solution, the second order reliability index obtained by the improved first order second moment method was used to obtain the new fourth order reliability index, so as to improve the reliability solution accuracy of single failure mode. Then, the correlation between multiple failure modes and the overall failure probability considering failure correlation were calculated based on the conditional probability dimension reduction method. Finally, taking the transmission gear of a system a a example, the calculation results of the proposed method, mean value first order second moment (MVFOSM) method, advanced first order second moment (AFOSM) method and traditional high-order moment standardization technique (HOMST) method were compared. The results show that the accuracy and efficiency of the proposed method are greatly improved, and it also provides a theoretical method to analyze the reliability of multiple failure modes.